2014
DOI: 10.1007/s00702-014-1199-x
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal journey of body and mind in Parkinson’s disease: the manifestations, risk factors and their relationship to daytime symptoms. Evidence from the NIGHT-PD study

Abstract: Nocturnal manifestations of Parkinson's disease (PD) are myriad, have diverse etiologies and include motor, sleep, urinary, and neuropsychiatric symptoms which are often associated with daytime somnolence. While most patients perceive these symptoms as troublesome, the recognition of nocturnal problems related to PD is still low in clinical practice. We conducted a survey using semi-structured interviews and self-rated questionnaires of 215 consecutive patients with PD enrolled in three centers in Thailand to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 42 publications
3
27
2
Order By: Relevance
“…Although the data cannot as yet be generalized, the results of axial nocturnal movements in our pilot study have identified several characteristics of the problems of rolling over among patients with PD, including less frequent turns, smaller turns, and slower turns when compared with matched spouses. These findings reinforce previous observations of nocturnal hypokinesia-mostly conducted in the form of questionnaires and interviewsshowing that impaired bed mobility exists and is likely to contribute to a wide range of nocturnal motor symptoms and NMSs in patients with PD, such as stiffness, rigidity, pain, breathing disorders, nocturia, or even insomnia [5,9,[18][19][35][36][37]. Moreover, a number of recent studies support the negative effects of nocturnal hypokinesia on the overall sleep quality, daytime symptoms, and quality of life of both patients as well as caregivers [5,7,[35][36][37].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Although the data cannot as yet be generalized, the results of axial nocturnal movements in our pilot study have identified several characteristics of the problems of rolling over among patients with PD, including less frequent turns, smaller turns, and slower turns when compared with matched spouses. These findings reinforce previous observations of nocturnal hypokinesia-mostly conducted in the form of questionnaires and interviewsshowing that impaired bed mobility exists and is likely to contribute to a wide range of nocturnal motor symptoms and NMSs in patients with PD, such as stiffness, rigidity, pain, breathing disorders, nocturia, or even insomnia [5,9,[18][19][35][36][37]. Moreover, a number of recent studies support the negative effects of nocturnal hypokinesia on the overall sleep quality, daytime symptoms, and quality of life of both patients as well as caregivers [5,7,[35][36][37].…”
Section: Discussionsupporting
confidence: 78%
“…Specific scales, such as the PDSS, the Pittsburgh Sleep Quality Index, and the Scales for Outcomes in PD-Sleep have been developed specifically to evaluate sleep and nocturnal disabilities in PD [20][21][22]. Recently, our group has modified the PDSS to capture more nocturnal symptom domains and provide evidence for the relationship between nocturnal manifestations of PD and daytime wearing-off [5]. With the advances in sensor technology, there is increased interest in the ambulatory assessment of symptoms in PD [23][24][25], but very few studies have been dedicated to the objective monitoring of nocturnal symptoms [26][27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas, we once very much focused on 'end-of-dose wearing-off', we now increasingly consider the time taken to ON, which is related to drug absorption and has been reported to be more than twice the duration of wearing-off [56]. Nocturnal hypokinesia and early morning off is often the longest OFF period in the daily treatment cycle [5,57], and delays to ON time and dose failures have been reported to account for >60% of daily OFF time [58]. As such, this provides a rationale for using non-oral therapies such as apomorphine injections or infusion which do not rely on GI absorption to manage motor fluctuations in patients where oral treatments do not provide sufficient control.…”
Section: Management Of Motor Complicationsmentioning
confidence: 99%
“…Nocturnal symptoms as well as early morning fluctuations (motor and NMS) remain neglected [5]. To move forward with medical management, it is important to consider new insights that recent research offers and in this review we examine how a better understanding of the disease pathology and progression might inform our daily clinical practice.…”
Section: Introductionmentioning
confidence: 99%